ACTIVE VIEW AGENTS FOR PERSONALIZED E-COMMERCE APPLICATIONS (Journal of Information and Communication Technology, 2003)
Giving the right information to the right person at the right time is one of the main factors contributing to the success of e-commerce applications. Existing applications of active views to e-commerce mostly generate application views based on user roles such as customers and vendors, so they cannot completely serve one-to-one marketing. Furthermore, the data controlled by the existing applications is limited to those retrieved from databases, but does not include other web contents such as pictures, descriptive information and hyperlinks. In addition, the integration of active views to existing e-commerce applications still presents some difficulties in tackling heterogenity. This work presents a model of the Active View Agents System (AVAS), based on a co-performance model of multi-agents, to resolve these problems.